2020
DOI: 10.1155/2020/2962138
|View full text |Cite
|
Sign up to set email alerts
|

Double Burden of Malnutrition: Examining the Growth Profile and Coexistence of Undernutrition, Overweight, and Obesity among School-Aged Children and Adolescents in Urban and Rural Counties in Henan Province, China

Abstract: Objective. To examine the gender, age, and region of residence in the anthropometric and nutritional profiles of children and adolescents aged 6–18 in Henan Province, China’s third most populous province. Design. This cross-sectional study of the China National Nutrition and Health survey (2010–2013) used a multistage cluster sampling technique. The sample included Chinese schoolchildren and adolescents aged 6 to 18 years (1,660 boys and 1,561 girls). Multiple logistic regression models were used to estimate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 32 publications
10
22
0
Order By: Relevance
“…There was, however, a disproportionately high prevalence of anemia in those with OWOB, which shows a clear coexistence of anemia and OWOB in this adolescent cohort. Similar to these findings, the coexistence of anemia and OWOB had been reported in many countries undergoing nutrition transition 53 55 . The combination of both anemia and obesity may affect adolescent growth and development, leading to psychological disorders, cognitive dysfunction, impaired motor abilities, altered timing of puberty, and multiple risk of comorbidities such as the metabolic syndrome and type 2 diabetes 55 , 56 .…”
Section: Discussionsupporting
confidence: 88%
“…There was, however, a disproportionately high prevalence of anemia in those with OWOB, which shows a clear coexistence of anemia and OWOB in this adolescent cohort. Similar to these findings, the coexistence of anemia and OWOB had been reported in many countries undergoing nutrition transition 53 55 . The combination of both anemia and obesity may affect adolescent growth and development, leading to psychological disorders, cognitive dysfunction, impaired motor abilities, altered timing of puberty, and multiple risk of comorbidities such as the metabolic syndrome and type 2 diabetes 55 , 56 .…”
Section: Discussionsupporting
confidence: 88%
“…Malnutrition is probably due to anorexia, nausea, vomiting, and diarrhea (which impair food intake and absorption), hypoalbuminemia, hypermetabolism, and excessive nitrogen loss [92,93]. These effects are clearly associated with the increase in pro-inflammatory cytokines observed in these patients.…”
Section: Protein-energy Malnutritionmentioning
confidence: 99%
“…In general, no association of CFM with the intake of speci c foods was reported. There is a global in ux of overweight/obesity together with undernutrition and micronutrient de ciency at the individual, household, and community level, due to changes in the dietary habits from low fat and high bre diet to high caloric, non-nutritious, low bre and high-fat food (82,83) . Studies conducted previously have shown that protein consumption can be effectively increased for the management of moderately acute malnourished (MAM) and severely acute malnourished (SAM) children (84) .…”
Section: Discussionmentioning
confidence: 99%